2018
DOI: 10.1016/j.ebiom.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Persistence in Ocular Tissues and Fluids (EVICT) Study: Reverse Transcription-Polymerase Chain Reaction and Cataract Surgery Outcomes of Ebola Survivors in Sierra Leone

Abstract: BackgroundEbola virus disease (EVD) survivors are at risk for uveitis during convalescence. Vision loss has been observed following uveitis due to cataracts. Since Ebola virus (EBOV) may persist in the ocular fluid of EVD survivors for an unknown duration, there are questions about the safety and feasibility of vision restorative cataract surgery in EVD survivors.MethodsWe conducted a cross-sectional study of EVD survivors anticipating cataract surgery and patients with active uveitis to evaluate EBOV RNA pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 19 publications
2
63
0
2
Order By: Relevance
“…Besides the eye, other immune privileged sites where Ebola virus persistence has been documented, with resultant clinical implications, include the central nervous system and reproductive organs [17,21,23]. Meningoencephalitis has been reported as a late sequela in an Ebola survivor [14] and sexual transmission was reported in association with viral persistence in West Africa [23,24].…”
Section: More Recently Zeng Et Al Evaluated Persistent Asymptomatmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the eye, other immune privileged sites where Ebola virus persistence has been documented, with resultant clinical implications, include the central nervous system and reproductive organs [17,21,23]. Meningoencephalitis has been reported as a late sequela in an Ebola survivor [14] and sexual transmission was reported in association with viral persistence in West Africa [23,24].…”
Section: More Recently Zeng Et Al Evaluated Persistent Asymptomatmentioning
confidence: 99%
“…To address this question, we designed the Ebola Virus Persistence in Ocular Tissues and Fluids (EVICT) Study [17]. In this study, 50 EVD survivors were recruited for ocular fluid sampling, the majority of whom required cataract surgery.…”
Section: Medical and Surgical Management Of Ophthalmic Sequelae Of Evdmentioning
confidence: 99%
“…A study of 96 Ebola virus disease survivors in Liberia found that three‐quarters reported blurry vision, while over half reported photophobia, tearing and/or eye pain . However, the main ocular complication of EBOV infection was uveitis, with over 180 cases being documented in survivors of the 2014‐2016 West African epidemic . Reported rates of uveitis in Ebola survivors vary, but the condition may affect as many as one‐third of these individuals, who present on average 3 to 8 wk after discharge from the Ebola treatment unit .…”
Section: Ebola Virus Diseasementioning
confidence: 99%
“…6 However, the main ocular complication of EBOV infection was uveitis, with over 180 cases being documented in survivors of the 2014-2016 West African epidemic. 6,68,72,[76][77][78][79] Reported rates of uveitis in Ebola survivors vary, but the condition may affect as many as one-third of these individuals, who present on average 3 to 8 wk after discharge from the Ebola treatment unit. 68,76,77 Risk factors for developing uveitis include a high viral load while in the treatment unit, presumed conjunctivitis during the acute phase of disease and older age.…”
Section: Post-ebola Uveitismentioning
confidence: 99%
See 1 more Smart Citation